Loading and unloading forces following addition of 5% Cu in nickel-titanium alloy used for orthodontics - Aphinan Phukaoluan (2018)
© 2017 Trans Tech Publications. This study aims to address the amount of force delivered by a fabricated NiTiCu orthodontic wire with a ternary composition ratio of 46.0 Ni: 49.0 Ti: 5.0 Cu and to compare the results with a commercial NiTiCu35°C orthodontic archwire. Nickel (purity 99.9%), Titanium (purity 99.8%), and Copper (purity 99.9%) were used in this study with the atomic weight ratio 46.0 Ni: 49.0 Ti: 5.0 Cu. The elements were melted to form an alloy using an electrolytic arc furnace in argon gas atmosphere and homogenized at 800°C for 1 hr. The alloys were subsequently sliced into thin plates (1.5mm) by EDM wire cutting machine to obtain the specimens and were cold-rolled with 30% reduction followed by heat treatment in a furnace at 400°C for 1 hour. Then, the three newly fabricated NiTiCu specimens were cut in nearly identical wire sizes of 0.016 inch x0.022 inch. Commercial preformed Ormco NiTiCu35°C archwire with size 0.016 inch x 0.022 inches were used for comparative purposes. Three-point bending test was performed using a Universal Testing Machine to investigate the force of the load-deflection curve at oral temperature (36°C+ 1) with deflection points at 0.25, 0.5, 0.75, 1.0, 1.25, and 1.5 mm. Descriptive statistics was used to evaluate each variable and independent t-test was used to analyze the differences between the groups. It was found that both NiTiCu wires presented typical superelastic properties as observed from the load-deflection curve. The average force was 341.70 g for loading, and 264.18 g for unloading for 46.0 Ni: 49.0 Ti: 5.0 Cu wire. Similarly, the values were 299.88 g for loading, and 201.96 g for unloading for Ormco NiTiCu35°C. There were significant differences (p<0.05) in mean loading and unloading forces between the two NiTiCu wires. The deflection forces in loading and unloading force for Ormco NiTiCu at each point were less than 46.0 Ni: 49.0 Ti: 5.0 Cu wire, except at the deflection point of 0.25 mm. Regarding the force difference between each deflection point of loading and unloading force, Ormco NiTiCu35°C exerted less force than 46.0 Ni: 49.0 Ti: 5.0 Cu wire, except at difference deflection at 1.5-1.25 mm of unloading force. However, there were still within the acceptable limits for orthodontic use. It is concluded that the fabricated ternary alloy of 46.0 Ni: 49.0 Ti: 5.0 Cu (atomic weight) with 30% reduction and heat treatment at 400°C for 1 hr. and Ormco 35°C NiTiCu presented the characteristics of both superelastic and shape memory in their wire form. The unloading forces of both NiTiCu wires were in the range of orthodontic use. This should be a good foundation for further studies towards development of new orthodontic NiTiCu archwires.